2018
DOI: 10.1016/j.jenvman.2018.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment of heavy metals in atmospheric deposition in a congested city environment in a developing country: Kandy City, Sri Lanka

Abstract: This research study which was undertaken in a congested city environment in a developing country provides a robust approach for the assessment and management of human health risk associated with atmospheric heavy metals. The case study area was Kandy City, which is the second largest city in Sri Lanka and bears the characteristics of a typical city in the developing world such as the urban footprint, high population density and traffic congestion. Atmospheric deposition samples were collected on a weekly basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…This result indicates that the high content of Zn mostly coincided with the discharge of domestic waste rather than coal mining activities. It was identified that high Zn loads were attributed to vehicular emissions and the wide use of Zn-coated building materials 47 . The Zn transportation characteristics were similar to those of Cd, with Zn transported by the combined actions of surface water and atmospheric deposition.…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that the high content of Zn mostly coincided with the discharge of domestic waste rather than coal mining activities. It was identified that high Zn loads were attributed to vehicular emissions and the wide use of Zn-coated building materials 47 . The Zn transportation characteristics were similar to those of Cd, with Zn transported by the combined actions of surface water and atmospheric deposition.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, parts of the sieved dust samples were transported to new self-sealing polyethylene bags and then stored at 4°C before analysis. According to previous assessments of the potential health risk of heavy elements to the human body (Men et al 2018b), seven typical metals (Li et al 2017;Lin et al 2019;Weerasundara et al 2018) and arsenic, an oncogenic metalloid (Rahman et al 2019;Škrbić et al 2018), which has some of the chemical properties of a metal, were chosen for determination. These eight elements are cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb), zinc (Zn), and arsenic (As).…”
Section: Experimental Analysismentioning
confidence: 99%
“…However, some of the topographical obstacles (mountain ranges and slopes) and malfunctioning of socioeconomic attributes (infrastructure and services) have been caused by the scarcity of livable resident land. The mean daytime temperature ranges from 28-32 • C, while the average rainfall is approximately 2085 mm (long-term) [20] and 52-398 mm (monthly) [18]. Except for a short, dry period, Kandy City is like other green cities and has a tropical equatorial climate and a monsoon rainfall pattern.…”
Section: Study Areamentioning
confidence: 99%
“…Thus, conducting this type of research is a timely vital task to identify the level of life quality of residents. In the process, we first identified the importance of Kandy City as a commercial and living place by exploring past research [19,20] and development plans [59]. However, research related to the quality of life or livability of the city was still lacking, and this was the motivation factor for selecting this research title.…”
Section: Urbanization and Its Effect On Life Quality In Kandy Citymentioning
confidence: 99%